(untitled) (Società e diritti, 2019)
Abstract In this work, a hypothesis of Dr. Francisco Miro Quesada Cantuarias on non-arbitrariness in politics is analyzed. This hypothesis has been empirically confirmed. Key words: Politis, empirical research, Francisco Miro Quesada Cantuarias